Activation‐induced cytidine deaminase regulates activity‐dependent BDNF expression in post‐mitotic cortical neurons. (17th July 2014) - Ratnu, Vikram S.; Wei, Wei; Bredy, Timothy W.
Abstract Activity‐dependent gene expression depends, in part, on transcriptional regulation that is coordinated by rapid changes in the chromatin landscape as well as the covalent modification of DNA. Here we demonstrate that the expression of brain‐derived neurotrophic factor (BDNF), a gene that is critically involved in neural plasticity and subject to epigenetic regulation, is regulated by the RNA/DNA editing enzyme, activation‐induced cytidine deaminase (AID). Similar to previous reports, we observed an activity‐dependent induction of BDNF exon IV mRNA expression, which correlated with a reduction in DNA methylation within the BDNF P4 promoter. Lentiviral‐mediated knockdown of AID disrupted these effects and inhibited BDNF exon IV mRNA expression, an effect that was associated with decreased cAMP response element‐binding protein occupancy within the BDNF P4 promoter. Thus, together with other epigenetic mechanisms, AID plays a key role in regulating activity‐dependent BDNF expression in post‐mitotic cortical neurons.